2011
DOI: 10.1016/j.jinsphys.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Digestive physiology and characterization of digestive cathepsin L-like proteinase from the sugarcane weevil Sphenophorus levis

Abstract: Sugarcane is an important crop that has recently become subject to attacks from the weevil Sphenophorus levis, which is not efficiently controlled with chemical insecticides. This demands the development of new control devices for which digestive physiology data are needed. In the present study, ion-exchange chromatography of S. levis whole midgut homogenates, together with enzyme assays with natural and synthetic substrates and specific inhibitors, demonstrated that a cysteine proteinase is a major proteinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
(29 reference statements)
3
17
0
Order By: Relevance
“…SDS-PAGE analysis revealed that purification of the cysteine peptidase from S. levis larvae was efficient, as demonstrated by the presence of a single band corresponding to a molecular mass of approximately 37 kDa (Soares-Costa et al, 2011). This information is in agreement with the expected molecular mass calculated from the EST clone (gene bank accession number FJ467290) coding for this cysteine peptidase.…”
Section: Mass Spectrometry Analysissupporting
confidence: 79%
See 2 more Smart Citations
“…SDS-PAGE analysis revealed that purification of the cysteine peptidase from S. levis larvae was efficient, as demonstrated by the presence of a single band corresponding to a molecular mass of approximately 37 kDa (Soares-Costa et al, 2011). This information is in agreement with the expected molecular mass calculated from the EST clone (gene bank accession number FJ467290) coding for this cysteine peptidase.…”
Section: Mass Spectrometry Analysissupporting
confidence: 79%
“…Both amino acid residues have hydrophobic side chains and therefore share similar Amino acid sequences were deduced from product ions and identified (bold) in the cysteine peptidase sequence deduced from S. levis ESTs obtained from the larval cDNA library, shown below. These data prove that the SlCathL clone (FJ467290) chosen for recombinant expression and characterization corresponds to the previous purified digestive enzyme (Soares-Costa et al, 2011). The peptide "VPESIDWR" (A) is a non-tryptic peptide, considering the preceding serine residue in the Sl-CathL protein sequence.…”
Section: Enzymatic Activity Of Rsl-cathlsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar functions of CatL in vitellogenesis were also found in rainbow trout Oncorhynchus mykiss (Kwon et al, 2001) and Danio rerio (Carnevali et al, 2006). Most studies on CatL in arthropods have focused on the function of CatL in immunity (Ren et al, 2010;Zhang et al, 2010b) and digestion (Hu and Leung, 2007;Soares-Costa et al, 2011), but little is known of its role in VTG utilization. Current evidence in Metapenaeus ensis (Crustacean) suggests that the ovary is the only non-alimentary organ showing CatL expression (Hu and Leung, 2004).…”
Section: Introductionmentioning
confidence: 65%
“…It has been revealed that cathepsin L-like enzymes are the only quantitatively important member of cysteine proteinases presented in midgut of insects. Digestive cathepsin L-like enzymes have been purified from Diabrotica virgifera (Coleoptera: Cucujiformia) (Koiwa et al, 2000), Acyrthosiphon pisum (Hemiptera: Sternorrhyncha) (Cristofoletti et al, 2003), T. molitor (Coleoptera: Cucujiformia) (Cristofoletti et al , 2005), Sphenophorus levis (Coleoptera: Curculionidae) (Soares-Costa et al, 2011;Fonseca et al, 2012), and Triatoma brasiliensis (Reduviidae, Triatominae) (Waniek et al, 2012).…”
Section: Insect Digestive Proteinasesmentioning
confidence: 99%